Review on the mixture design and mechanical properties of the lightweight concrete containing expanded polystyrene beads. Issue 1 (2nd January 2018) - Vakhshouri, Behnam; Nejadi, Shami
Abstract: Lightweight concrete containing expanded polystyrene beads (EPS-LWC) is frequently used in different structural and non-structural applications, since it was first developed about 60 years ago. However, effect of new materials and admixtures to improve its performance and strength are not investigated properly. A wide range of investigations about EPS-LWC since 1976, including the experimental data are evaluated. The collected data contain the information of curing methods, type of fine and coarse aggregates, mineral fillers, chemical admixtures and fibres in each experiment. In addition, the mixture proportions including the size and volume of EPS beads, density and compressive strength of the concrete are presented. Mechanical properties of EPS-LWC from 154 mixture design in 55 experimental programmes are also assessed. Utilising the experimental data, new models are developed and verified by the existing models of the mechanical properties of concrete. The existing models of the mechanical properties of LWC are also compared with those of the convention concrete.